How do you simplify (7y -x)^2?

3 Answers
Jan 25, 2017

49y^2 + x^2 - 14xy

Explanation:

It is a binomial squared:

(a + b)^2 = a^2 + b^2 + 2ab

Jan 25, 2017

See below.

Explanation:

This is a binomial so we can make use of the standard formula

(color(red)"a"-color(blue)"b")^2 = color(red)"a"^2 - 2color(red)"a"color(blue)"b" + color(blue)"b"^2

For our purposes, color(red)("a"=7y and color(blue)("b"=x . Putting the values in the above given equation we obtain:

(7y -x)^2 = 49y^2 -2*7y*x + x^2

=> (7y -x)^2 = 49y^2 -14xy + x^2

Jan 25, 2017

49y^2-14yx+x^2

Explanation:

(7y-x)^2

color(white)(aaaaaaaaaaaaa)7y-x

color(white)(aaaaaaaaaaaaa)7y-x

color(white)(aaaaaaaaaaa)---

color(white)(aaaaaaaaaaaaa)49y^2-7yx

color(white)(aaaaaaaaaaaaaaaaa)-7yx+x^2

color(white)(aaaaaaaaaaaaa)------

color(white)(aaaaaaaaaaaa)49y^2-14yx+x^2